Three-dimensional echocardiography - Buck, Thomas MD; Franke, Andreas; Monaghan, Mark J. (Springer-Verlag Berlin Heidelberg, 2011)
Three-dimensional echocardiography is the most recent fundamental advancement in echocardiography. Since real-time 3D echocardiography became commercially available in 2002, it has rapidly been accepted in echo labs worldwide. This book covers all clinically relevant aspects of this fascinating new technology, including a comprehensive explanation of its basic principles, practical aspects of clinical application, and detailed descriptions of specific uses in the broad spectrum of clinically important heart disease. The book was written by a group of well-recognized international experts in the field, who have not only been involved in the scientific and clinical evolution of 3D echocardiography since its inception but are also intensively involved in expert training courses. As a result, the clear focus of this book is on the practical application of 3D echocardiography in daily clinical routine with tips and tricks for both beginners and experts, accompanied by more than 150 case examples comprehensively illustrated in more than 800 images and more than 500 videos provided on a DVD. In addition to an in-depth review of the most recent literature on real-time 3D echocardiography, this book represents an invaluable reference work for beginners and expert users of 3D echocardiography. Tips and tricks for beginners and experts Educational material for 3D training courses Comprehensively illustrated cases DVD with video clips of all sample cases.